Evidence for the Dual Role of Floral Secretory Cells in Bulbophyllum - Stpiczyńska, Małgorzata; Davies, Kevin L. (Acta Biologica Cracoviensia s. Botanica, 2016)
Abstract Floral epidermal cells of most species of Bulbophyllum Thouars studied to date produce both lipid-rich food-rewards and fragrance. Since fragrances largely consist of terpenoids and have an affinity for lipophilic stains, the simultaneous presence of lipid-rich food-rewards frustrates identification of fragrance-secreting cells by conventional histochemistry. Furthermore, since both lipid-rich food-rewards and fragrances are probably synthesized by a similar complement of organelles, interpretation of TEM images can prove difficult. All members of section Racemosae Benth. & Hook. f. investigated to date, however, are unusual in their secretion of a predominantly proteinaceous food-reward, and lipids are seemingly absent. This might enable their use as models for the identification and characterization of fragrance-secreting tissues and organelles. Three members of sect. Racemosae were chosen, namely Bulbophyllum dissitiflorum Seidenf., B. lilacinum Ridl. and B. tricorne Seidenf. & Smitinand. All produced food-rewards. Of these, one (B. dissitiflorum) lacked fragrance and was used as a control, whereas the remaining two species produced fragrance. Having established that the food-reward was mainly proteinaceous in each case, and did not test positively for lipid, we undertook further histochemical investigations, as well as light microscopy, SEM and TEM. Specialized palisade-like epidermal cells of all species contained protein bodies and rough endoplasmic reticulum consistent with the production and secretion of a protein-rich food-reward. Cuticular pores were also present. In fragrant species, these cells also contained abundant smooth endoplasmic reticulum, oil droplets and many, well-developed, spherical plastids with numerous plastoglobuli, similar to those found in the osmophores (fragrance-producing structures) of other orchids. Indeterminate, osmiophilic cytoplasmic inclusions were also present. By contrast, the non-fragrant species lacked oil droplets and other osmiophilic inclusions and the plastids were scant, poorly developed, often elongate or irregular in shape and contained few plastoglobuli. Smooth endoplasmic reticulum was also less frequent. Since food-rewards tested negatively for lipid, it is probable that any oil droplets present were involved in fragrance production, especially since they were absent from the non-fragrant species. Thus, the unusual absence of lipids from the food-rewards of sect. Racemosae provided a rare opportunity, permitting, for the first time, the unraveling of these two secretory processes (food-reward and fragrance) in Bulbophyllum and clearly demonstrating the plasticity of these cells and their dual role in secretion.